Crohn’s Disease – The Pathogenesis of a Granulomatous Vasculitis: A Hypothesis - Andrew J Wakefield (Canadian Journal of Gastroenterology)
Dissatisfied with traditional approaches to studying the pathogenesis of Crohn’s disease, the author and colleagues proposed and developed the hypothesis that Crohn’s disease is a granulomatous vasculitis mediated by a persistent viral infection of the mesenteric microvascular endothelium. Employing a range of techniques, the mesenteric vascular anatomy of intestine affected by Crohn’s disease was studied and the presence of a widespread multifocal vasculitis was demonstrated. Based upon certain behavioural characteristics of measles virus, including its tropism for intestinal endothelium and its ability to persist in human tissues, this agent was sought by in situ hybridization, electron microscopy and immunohistochemistry. The virus was detected in foci of granulomatous and lymphocytic inflammation. Recent epidemiological data from Sweden support the idea that early exposure to measles virus is a risk factor for the later development of Crohn’s disease. These data are consistent with the possibility of a persistent measles virus enteritis in the etiology and pathogenesis of Crohn’s disease and this hypothesis merits further study.